2016
DOI: 10.1136/esmoopen-2016-000122
|View full text |Cite
|
Sign up to set email alerts
|

The promise of immunotherapy in head and neck squamous cell carcinoma: combinatorial immunotherapy approaches

Abstract: The immune system plays a fundamental role in preventing cancer development by recognising and eliminating tumour cells. The recent success in the field of immunotherapy has confirmed the potential to exploit the immune response as a cancer treatment. Head and neck squamous cell carcinoma (HNSCC) is a malignancy characterized by dismal prognosis and high mortality rate; low survival outcomes in combination with significant toxicity of current treatment strategies highlight the necessity for novel therapeutic m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
42
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(45 citation statements)
references
References 99 publications
(86 reference statements)
0
42
0
Order By: Relevance
“…12 Immunotherapy for head and neck cancer using anticytotoxic T-lymphocyte-associated antigen-4 (CTLA-4) Ab and anti-programmed death-1 (PD-1) Ab are ongoing. 13,14 Head and neck cancer contains large numbers of somatic mutations which can generate neoantigens to activate cytotoxic CD8 + T cells. [15][16][17] However, over half of patients do not receive the benefits of immunotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…12 Immunotherapy for head and neck cancer using anticytotoxic T-lymphocyte-associated antigen-4 (CTLA-4) Ab and anti-programmed death-1 (PD-1) Ab are ongoing. 13,14 Head and neck cancer contains large numbers of somatic mutations which can generate neoantigens to activate cytotoxic CD8 + T cells. [15][16][17] However, over half of patients do not receive the benefits of immunotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…The use of checkpoint inhibitors in the management of patients with head and neck squamous cell carcinoma (HNSCC) has become increasingly common following successful early clinical trials. Additionally, it has been shown that blockade of programmed death‐1 (PD‐1) and/or programmed death ligand‐1 (PD‐L1) has positive therapeutic benefits in HNSCC patients . Moreover, PD‐1 and PD‐L1 have emerged as the key checkpoints that can be manipulated with inhibitory monoclonal antibodies.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, it has been shown that blockade of programmed death-1 (PD-1) and/or programmed death ligand-1 (PD-L1) has positive therapeutic benefits in HNSCC patients. [1][2][3][4][5][6][7] Moreover, PD-1 and PD-L1 have emerged as the key checkpoints that can be manipulated with inhibitory monoclonal antibodies. In this context, the expression profile of PD-L1 is typically evaluated to identify patients who can clinically benefit from such inhibitors.…”
Section: Introductionmentioning
confidence: 99%
“…In conclusion, our results demonstrated that ICM function in the immune‐checkpoint system but also have important roles for the elicitation of eTreg activation and functions, which might create a tumor suppressive immune microenvironment in HNSCC tissues. Many combination immunotherapies with immune‐checkpoint inhibitors are being investigated in clinical trials for HNSCC 59 . It is important to choose drug combinations that effectively inhibit eTreg functions and immune‐checkpoint systems to improve HNSCC immunotherapy.…”
Section: Discussionmentioning
confidence: 99%